2017
DOI: 10.1371/journal.pone.0186735
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial and influenza viruses in children under 2 years old with severe acute respiratory infection (SARI) in Maputo, 2015

Abstract: IntroductionAlthough respiratory syncytial virus (RSV) and influenza virus (influenza) infections are one of the leading causes of Severe Acute Respiratory Infections (SARI) and death in young children worldwide, little is known about the burden of these pathogens in Mozambique.Material and methodsFrom January 2015 to January 2016, nasopharyngeal swabs from 450 children, aged ≤2 years, who had been admitted to the Pediatric Department of the Maputo Central Hospital (HCM) in Mozambique, suffering with SARI were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…In contrary to the high RSV rate in western settings [ 29 ] and a study from Ghana [ 18 ], we documented RSV infection in only a fifth of all infant ALRI and about a third of bronchiolitis cases.RSV prevalence in our study was similar to a study in Maputo [ 30 ], but higher than other studies documenting 9–15% prevalence [ 10 , 20 22 ]. While the strict exclusion of risk populations may affect our prevalence rate, the younger age of our patients (less than 6 months) may also be the reason for higher prevalence compared to the previous African studies [ 20 22 ].…”
Section: Discussionsupporting
confidence: 89%
“…In contrary to the high RSV rate in western settings [ 29 ] and a study from Ghana [ 18 ], we documented RSV infection in only a fifth of all infant ALRI and about a third of bronchiolitis cases.RSV prevalence in our study was similar to a study in Maputo [ 30 ], but higher than other studies documenting 9–15% prevalence [ 10 , 20 22 ]. While the strict exclusion of risk populations may affect our prevalence rate, the younger age of our patients (less than 6 months) may also be the reason for higher prevalence compared to the previous African studies [ 20 22 ].…”
Section: Discussionsupporting
confidence: 89%
“…Studies on S&S of RSV in the pediatric population (25 studies) took place in both community and clinical settings, and S&S were reported by both caregivers (six studies) 19 , 20 , 21 , 39 , 40 , 41 and clinicians (22 studies) 19 , 20 , 21 , 26 , 27 , 28 , 29 , 34 , 35 , 37 , 38 , 39 , 40 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ; we analyzed and present these two sets separately. In addition, two publications presented clinician‐reported S&S in the intensive care unit (ICU).…”
Section: Resultsmentioning
confidence: 99%
“…The most common cause of SARI in children is viral infections [5][6][7][8][9][10], including influenza viruses A and B (Flu A/B); respiratory syncytial virus (RSV); adenovirus (ADV); parainfluenza virus (PIV) 1-3; picornavirus (PIC), which mainly includes human rhinovirus (RV) and human enterovirus (EV); human coronaviruses (HCoV), which includes OC43, 229E, NL63, and HKU; human bocavirus (HBoV); and human metapneumovirus (HMPV). Although the viral and epidemiological profiles of pediatric patients with SARI vary among countries [4,[7][8][9][10][11][12][13][14][15], few studies have comprehensively compared the viral and epidemiological profiles of pediatric patients with SARI in different geographic areas or climate zones within the same country, such as China.…”
Section: Introductionmentioning
confidence: 99%